Classic Jewelry Aesthetics on Payas Agung Badung - A.A.Ngr. Anom Mayun Konta Tenaya (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2022)
Jewelry is an important and inseparable part of Payas Agung Badung's clothing. In the past, the nobles of the Badung kingdom had exclusive rights to Payas Agung (Balinese Traditional Uniform) which were used only at certain times, such as religious rituals and traditional events. Payas Agung Badung is still used today. specifically for weddings and tooth-filling in the Badung district and Denpasar city. The unique nature of this dress does not only come from the material and design aspects but also from the socio-cultural aspect, especially the artistic value of Payas Agung Badung clothing, which has a strong character. Traditional fabrics harmoniously blend with Balinese jewelry. The focus of this research is on jewelry which is the center of attention of the overall appearance of Payas Agung Badung. This research is a qualitative study using aesthetic theory. The primary data was obtained from the jewelry used at Payas Agung Badung in the period from 1930 to 1970. The secondary data were photographs belonging to the Puri Anom family in Denpasar. The results showed that the beauty of jewelry at Payas Agung Badung comes from intrinsic values, such as raw materials and motifs, as well as extrinsic values, such as the pakem (aesthetic principles) and deep meaning of the jewelry.